2019
DOI: 10.22495/cocv17i1siart5
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance in extreme institutional environment: Evidence from emerging economy

Abstract: Corporate governance (CG) is often split among rule and principle-based methods to regulation in distinctive institutional contexts. Relying on an alternative theoretical framework (i.e. institutional theory), rather than the dominant agency theory, this study conceptualizes corporate governance practices and structures as institutionally resolute and directed and explores the key institutional determinants of good CG practices in an emerging economy. Drawing on qualitative and quantitative methods, this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 125 publications
0
2
0
Order By: Relevance
“…The literature is pointed out that institutional determinants like legal, political, corruption level, cultural and values are very important to determine practices of CG in developed and developing countries (Arslan and Alqatan, 2020;Arslan et al, 2019). This argument also supports that the institutional environment of the country does not only affect the institutions directly but also indirectly by moderating the role of CG (Young et al, 2008).…”
Section: Institutional Quality and Risk Takingmentioning
confidence: 71%
“…The literature is pointed out that institutional determinants like legal, political, corruption level, cultural and values are very important to determine practices of CG in developed and developing countries (Arslan and Alqatan, 2020;Arslan et al, 2019). This argument also supports that the institutional environment of the country does not only affect the institutions directly but also indirectly by moderating the role of CG (Young et al, 2008).…”
Section: Institutional Quality and Risk Takingmentioning
confidence: 71%
“…Few studies are, Wu et al (2019) on US institutions, Joudi et al (2019) on Iranian firms, and Tahir et al (2019) on Pakistani listed firms, the relationship between CG and disclosure quality of listed Pakistani institutions investigated by Nosheen and Sajjad (2018), Musovaa (2017) on listed firms of Bratislava Stock Exchange. Arslan and Alqatan (2020) and Arslan et al (2019) concluded that institutional determinants like legal, political, corruption, culture and values are very important to determine the practices of CG in developed and developing countries. Given literature mainly focuses on the non-financial sector, however, the financial sector found little focus.…”
Section: Introductionmentioning
confidence: 99%